Lesson Study in Pre-Service Biology Teacher Education at Universitas Riau - Suryawati, Evi; Rahmi, Fitri Olvia; Dianti, Putri Rahma; Harfal, Zaldi; Nengsih, Dwi Tira (Journal of Learning Improvement and Lesson Study, 2024)
The Teacher Professional Education (TPE) Program aims to train qualified teachers by providing structured training and learning programs through Field Experience Practice (EP), which was implemented in schools in two cycles: EP 1 and EP 2, using the Lesson Study format. Both cycles of EP involved 1 tutor teacher, 2 observer teachers, 1 supervising lecturer, and 5 TPE students. Each cycle goes through 3 phases: Plan, Do, and See. The results of profiling showed that the students' characteristics were kinesthetic and audio-visual. The learning model used is problem-based learning, and based on observations of independent learning activities and collaboration in completing their assignments, all deficiencies are addressed during reflection activities. In the final stage of the learning activities, each party involved in the Lesson Study activities obtained valuable lessons. The supervisors received insights to apply improvements to courses related to the TPE program